Hubungan Tingkat Pengetahuan dengan Sikap dan Tindakan Ibu dalam Pencegahan Stunting di Kabupaten Natuna - Jaya, Jaya; Maryam, Syarifah; Asnia, Asnia; Kasim, Setiawan; Liliskarlina, Liliskarlina (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Stunting remains a major public health problem in Indonesia, particularly in remote island regions such as Natuna Regency. This condition is influenced by several factors, including mothers’ level of knowledge, attitudes, and practices regarding stunting prevention. This study aimed to analyze the relationship between knowledge level and mothers’ attitudes and practices toward stunting prevention in Natuna Regency in 2025. This research was an analytical observational study with a cross-sectional design involving 365 mothers with children under five. Samples were selected using a proportionate stratified random sampling technique. Data were collected through a structured questionnaire that had been tested for validity and reliability, and analyzed using the Chi-Square test at a 95% confidence level. The results showed that most respondents had good knowledge (69.6%), good attitudes (74.5%), and good preventive practices (53.7%) regarding stunting. The Chi-Square test revealed a significant relationship between knowledge level and preventive practices p = 0.0002), as well as between knowledge level and attitudes (p = 0.001). Mothers with higher knowledge levels tended to demonstrate more positive attitudes and preventive actions toward stunting compared to those with moderate or poor knowledge. In conclusion, increasing maternal knowledge plays an important role in shaping positive attitudes and preventive behaviors toward stunting, highlighting the need for continuous education and family nutrition counseling programs in Natuna Regency. Keywords : Stunting; knowledge; attitude; practice; mothers